Staying Preferences by Street Children in Surat City - Patel , NB; Desai , Toral; Bansal , RK; Thakar, Girish (National Journal of Community Medicine, 2011)
India houses the largest number of street children in the world. These children often live in abject poverty and squalid conditions. The present study aims to explore their staying preferences in the city of Surat and the reasons thereof. This cross-sectional study was conducted by interviewing 326 street children in Surat city. The study found that street children prefer to stay and work in Surat city as they perceive that Surat is a safer city; it is easier to earn money in this city; life and assimilation also is easier; there is less harassment by older children, police and others. The maximum numbers of street children are staying on the railway platforms 115 (35.3%). The major reasons given by the street children for choosing their place of stay are safety, convenience of finding work, comfortable shelter characteristics, availability of friends, and less harassment. There is a need to build mechanisms to increase safety of the street children at their places of stay and check their abuse by older children, police and authorities and encourage their stay at day care (24-hour care) centres.